PENINGKATAN HASIL BELAJAR IPA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA MURID KELAS IV SD INPRES BORONG JAMBU II - Herlinah, Herlinah; Afni, Nur; Wahid , Abdul (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2023)
This research is a Classroom Action Research conducted at SD Inpres Borong Jambu II which aims to improve learning outcomes in natural sciences. Makassar in the odd semester of the 2022/2023 school year with a total of 25 students. Data collection was carried out using student learning achievement tests and observation sheets. From the data collected then analyzed quantitatively and qualitatively. The results of the research were achieved after being analyzed, namely: 1) In cycle I, the average score of learning outcomes in Science The concept of the Nature and Changes in Shape of Objects was obtained at 62.8 at an ideal score of 100. 2) In cycle II, the average score of learning outcomes was obtained The Science Concept of the Nature and Change of Shape of Things is 85.6 with an ideal score of 100. From the results of this study, it can be generally concluded that there is an Increase in Science Learning Outcomes of the Concept of the Nature and Change of Shape of Things Through the STAD Type Cooperative Learning Model in Grade IV Students of SD Inpres Borong Jambu II, Manggala District, Makassar City.